2018
DOI: 10.1016/j.jid.2018.02.029
|View full text |Cite
|
Sign up to set email alerts
|

CCN1/Cyr61 Stimulates Melanogenesis through Integrin α6β1, p38 MAPK, and ERK1/2 Signaling Pathways in Human Epidermal Melanocytes

Abstract: Fibroblast-derived melanogenic paracrine mediators are known to play a role in melanogenesis. To investigate the effect of CCN1 (also called CYR61 or cysteine-rich 61) on melanogenesis, normal human epidermal melanocytes were treated with recombinant CCN1 protein. Our findings show that CCN1 activates melanogenesis through promoting melanosome maturation and up-regulation of MITF, TRP-1, and tyrosinase via the integrin α6β1, p38 MAPK, and ERK signaling pathways. Furthermore, we found that UVB irradiation stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 55 publications
1
13
0
1
Order By: Relevance
“…Jun et al reported that in the course of cutaneous wound repair, the highly expressed CCN1 in granulation tissue would promote the senescence of fibroblasts and regulate the expressions of anti‐fibrotic genes to suppress the fibrosis . Xu et al found that ultraviolet B irradiation could stimulate the secretion of CCN1 in normal human dermal fibroblasts . Our results revealed that both HA ceramics could also stimulate the CCNI secretion to induce the senescence of HSF cells, as was influenced by the surface microstructure of the ceramics.…”
Section: Discussionsupporting
confidence: 51%
“…Jun et al reported that in the course of cutaneous wound repair, the highly expressed CCN1 in granulation tissue would promote the senescence of fibroblasts and regulate the expressions of anti‐fibrotic genes to suppress the fibrosis . Xu et al found that ultraviolet B irradiation could stimulate the secretion of CCN1 in normal human dermal fibroblasts . Our results revealed that both HA ceramics could also stimulate the CCNI secretion to induce the senescence of HSF cells, as was influenced by the surface microstructure of the ceramics.…”
Section: Discussionsupporting
confidence: 51%
“…These results implicate neuregulin-1 in determining constitutive pigmentation, and suggest that it contributes to eumelanin synthesis, which is abundant in dark skin. Another melanogenic factor derived from fibroblasts is CCN1/Cyr61, an extracellular matrix (ECM) protein that was recently reported to increase melanogenesis via binding to integrin α6β1 and activating the MAP kinases p38 and ERK1/2 [ 106 ]. Secretion of CCN1/Cyr61 is enhanced following UV exposure, suggesting that this factor participates in the tanning response of melanocytes to UV.…”
Section: Paracrine Factors As Regulators Of Melanogenesis and The mentioning
confidence: 99%
“…The reductions in Netrin‐1 and FGF5 may also contribute to decreased expression of age spots as they decrease melanocyte migration . As we observed a decreased age spot expression clinically following the HSA treatment these changes in vitro must override any positive effects on melanocytes induced by Cyr61 and DKK .…”
Section: Discussionmentioning
confidence: 61%